Perbandingan Evaluasi Biaya Pengembangan Sistem Antrian RSUD Dr Soetrasno Rembang Menggunakan Metode Use Case Point dan Function Point (Studi Kasus: CV Pabrik Teknologi) - Dhya Fairuzu Zahiroh; Mochamad Chandra Saputra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The problem in a project is the calculation of the estimated costs doesn't have standards for calculating the cost, and suggested in the construction project refers to the execution of a structured on the Work Breakdown Structure (WBS). This research lays out the phase using WBS and scheduling of Sistem Antrian RSUD Dr. Soetrasno Rembang using Gantt Chart, as well as the calculation of the estimated costs of using Use Case Point and Function Point. The calculation of the Use Case Point needs Use Case Diagrams and Use Case Scenario so as to produce hours of effort is 2.850 hours and the estimated total cost is Rp 157.843.750, 00. While Function Point needs Data Flow Diagram so as to produce the effort 24 people during the nine months and the estimated total cost is Rp 200.650.000, 00. The result can help CV Pabrik Teknologi in solving the problem with comparison between Use Case Point, Function Point and Guesstimate.